An investigation into the interaction between piplartine (piperlongumine)and human serum albumin - de Alcântara-Contessoto, Nayara Sousa [UNESP]; Caruso, Ícaro Putinhon [UNESP]; Bezerra, Daniel Pereira; Filho, José Maria Barbosa; Cornélio, Marinônio Lopes [UNESP] (Elsevier, 2019)
Piplartines are alkaloid amides present in the roots and stems of different pepper species which have promising pharmacological properties including cancer prevention. Some recent studies have determined pharmacokinetic parameters of piplartine in rat blood plasma but without pointing to any molecular target or describing the physicochemical forces of the interaction. The present study investigated the interaction between piplartine and human serum albumin (HSA)the predominant protein in blood plasma. Fluorescence spectroscopy was utilized to observe the complex HSA-piplartine formation. Thermodynamic parameter analysis indicates that the process occurs spontaneously and is enthalpically driven; the affinity constant suggests that this interaction is reversible. This was reinforced by the binding density function method and by the displacement analysis that the piplartine binds on HSA at a single site, which was determined to be the IIA sub-domain. In silico analysis (molecular docking)identified the main residues involved in binding and the corresponding forces, which corroborates well with the experimental results.
Keywords: Fluorescence spectroscopy; Human serum albumin; Molecular docking; Piperlongumine; Piplartine